Kesiapan Penerapan Rekam Medis Elektronik Di Instalasi Rawat Inap RSIA IBI Surabaya - Annisa Damayanti Afandi; Diah Wijayanti Sutha; Sulistyoadi; Fardhan Imani (Jurnal Kesehatan, 2025)
Permenkes No. 24 of 2022 concerning the use of RME which is already mandatory in all health facilities. This study aims to analyze the readiness of the application of electronic medical records using the DOQ-IT method in inpatient installations. This type of research is quantitative analytic with the Spearman correlation test using a research instrument in the form of a questionnaire. A total of 19 populations were used in this study and purposive sampling was applied as a sampling technique by determining 15 samples to be used. The research variables used in this study are organizational culture, human resources, infrastructure, and leadership governance. It can be concluded from the results of the study that the readiness of the human resources sector obtained an average score of 19.7, with a fairly ready category, the readiness of the organizational work culture sector obtained an average score of 42.9, with a very ready category, the readiness of the leadership governance sector obtained an average score of 32.1, with a very ready category, the readiness of the infrastructure sector obtained an average score of 15.9, with a very ready category. All aspects are very ready to implement electronic medical records. Based on the total average score obtained of 110.6, it can be concluded that RSIA IBI Surabaya officers have a high level of readiness in implementing RME and are classified as very ready.  Keywords: Readiness, Electronic Medical Records, DOQ-IT, Hospitalization, Hospital.